Assessment of knowledge and usage of HIV post exposure prophylaxis among healthcare workers in a regional hospital in Ghana. (2018) - Babanawo, Felicia; Ibrahim, Abdallah; Bahar, Ozge Sensoy; Augustine, Augustine; Maya, Ernest
No abstract available